Perkembangan Modal Melalui Tradisi Mejejaitan Pada Perempuan Bali Di Desa Budakeling - Primayuli Mahayani, Ni Wayan Ayu; Kebayantini, Ni Luh Nyoman; Suka Arjawa, I Gst. Putu Bagus (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT Banten is one of the means of offering to God in Hindu religious rituals that have supporting components, namely jejaitan obtained through mejejaitan activity. The density of religious rituals makes the need for jejaitan higher. This becomes one of the factors of the emergence of jejaitan seller and the development of capital in society. Referring to the problem, the title of Capital Development in Mejejaitan Tradition was chosen to be examined. There are two problems in this research, namely 1) how the tradition of mejejaitan implemented ?, 2) how the development of capital in traditions mejejaitan? This research uses descriptive-explanantive type of research and located in Budakeling Village. Based on the results of the research, it is known that the tradition of mejejaitan in Budakeling Village is done steadily through the formation of inherited habitus from generation to generation. Along with the formation of this habitus, mejejaitan as cultural capital has developed. Mejejaitan is now transformed into economic capital through a production activity. Keywords: women; mejejaitan; capital; Bourdieu's structuralism.